2022
DOI: 10.1128/aac.02310-21
|View full text |Cite
|
Sign up to set email alerts
|

Combination of Mycobacterium tuberculosis RS Ratio and CFU Improves the Ability of Murine Efficacy Experiments to Distinguish between Drug Treatments

Abstract: Murine tuberculosis drug efficacy studies have historically monitored bacterial burden based on CFU of Mycobacterium tuberculosis in lung homogenate. In an alternative approach, a recently described molecular pharmacodynamic marker called the RS ratio quantifies drug effect on a fundamental cellular process, ongoing rRNA synthesis.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 22 publications
(31 reference statements)
0
14
0
Order By: Relevance
“…For example, regimens that have identical effects on CFU in mice can have different long-term relapse outcomes. 10,74 In previous studies, we demonstrated that quantification of rRNA synthesis via the RS ratio showed proof of concept that molecular measures of bacterial cellular processes in vivo can distinguish regimens that are indistinguishable based on CFU. 10,74 SEARCH-TB advances molecular characterization of drug effects in vivo to a higher level of granularity.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…For example, regimens that have identical effects on CFU in mice can have different long-term relapse outcomes. 10,74 In previous studies, we demonstrated that quantification of rRNA synthesis via the RS ratio showed proof of concept that molecular measures of bacterial cellular processes in vivo can distinguish regimens that are indistinguishable based on CFU. 10,74 SEARCH-TB advances molecular characterization of drug effects in vivo to a higher level of granularity.…”
Section: Discussionmentioning
confidence: 87%
“…10,74 In previous studies, we demonstrated that quantification of rRNA synthesis via the RS ratio showed proof of concept that molecular measures of bacterial cellular processes in vivo can distinguish regimens that are indistinguishable based on CFU. 10,74 SEARCH-TB advances molecular characterization of drug effects in vivo to a higher level of granularity. Others have demonstrated the power of Mtb transcriptional readouts of drug effect to predict drug interactions in vitro.…”
Section: Discussionmentioning
confidence: 87%
“…The EBA of rifampicin was evaluated using all available CFU and TTP data simultaneously, which further supported a strong mechanistic approach when developing the work and assessing the drug efficacy. Studies have shown that the combined use of two biomarkers better ranked the efficacy between treatments compared to using only one biomarker, as in the case of the combined use of CFU and RS ratio ( Dide-agossou et al, 2022 ). Liquid media are known to be more sensitive in detecting the Mtb populations than solid media but are more prone to contamination ( Cruciani et al, 2004 ; Diacon et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…Separate from investigation of it’s predictive capacity, the Isserlis formula provided a deconstruction of the PD effects of BPaL as a sum of effects arising from single-drug and pairwise products. The PD effects were also characterized for each drug component by a kill rate constant for bactericidal activity, and RS ratio half-life and equilibration as a measure of rRNA synthesis (16, 25). The interactions were quantified over time as deviations from Bliss and Isserlis formulas, with the latter including mutual interactions in contrast to the former which did not.…”
Section: Discussionmentioning
confidence: 99%